Peningkatan Hasil Belajar Siswa Kelas IV Dengan Menggunakan Model PJBL Di SD Negeri Terusan 1 Sindang - Arief Hidayat Afendi; Kurinih Kurinih; Adinda Putri Salsahbilla; Anandhita Stefhanie; Dzaimatun Atikah; liesse Lisnawati (Mathematics Education Study Program, 2025)
This research aims to improve the science learning outcomes of class IV students at SDN Terusan 1 Sindang through the Project Based Learning (PJBL) learning model. This classroom action research involved 41 students and used quantitative methods. The research results show a significant increase in student learning outcomes, from an average of 65 to 82. The PJBL model is effective in increasing student understanding and critical thinking skills